16 Del. Laws 716 (1879) - (:unkn) unknown (My University, 1881)
Ch. 548, § 1: Prohibited the carrying of concealed deadly weapons or selling deadly weapons other than an ordinary pocket knife to minors. Punishable by a fine of $25-200 or imprisonment for 10-30 days.
Keywords: CARRY - CONCEALED; TRANSFER - MINORS